The Role Of Communication And Information Media In Realizing National Development - Rahil Fauzan (Pena Cendekia Insani, 2020)
Communication and information media is social media in the form ofsocial networks as very effective media, namely communication andinformation media to convey problems or aspirations of thecommunity, especially for areas that have not been fully touched bythe media and are not widely known by the wider community,especially regional officials who are in office This study has thefollowing objectives: First, to describe the characteristics of thedigital era society that uses communication media. Second, describesthe interest of communication media with national development andThird, describes the opportunities and challenges that arise in societyin the digital era. And Fourth, describe the efforts that must be madein the digital era. Socialization Activities Development programs areno longer enough to rely solely on conventional media (newspapers,magazines, etc.). But it must be able to take advantage of internetbased media, so that development communication can beinstantaneous (real time) and two-way (interactive). According to theMinistry of Education and Culture, social media such as Whatsapp,Facebook and YouTube have been actively used by most people.